Ganaxolone versus Phenobarbital for Neonatal Seizure Management. Issue 6 (26th September 2022) - Miller, Suzanne L.; Bennet, Laura; Sutherland, Amy E.; Pham, Yen; McDonald, Courtney; Castillo‐Melendez, Margie; Allison, Beth J.; Mihelakis, Jamie; Nitsos, Ilias; Boyd, Ben J.; Hirst, Jonathan J.; Walker, David W.; et al.
Abstract : Objective: Seizures are more common in the neonatal period than at any other stage of life. Phenobarbital is the first‐line treatment for neonatal seizures and is at best effective in approximately 50% of babies, but may contribute to neuronal injury. Here, we assessed the efficacy of phenobarbital versus the synthetic neurosteroid, ganaxolone, to moderate seizure activity and neuropathology in neonatal lambs exposed to perinatal asphyxia. Methods: Asphyxia was induced via umbilical cord occlusion in term lambs at birth. Lambs were treated with ganaxolone (5mg/kg/bolus then 5mg/kg/day for 2 days) or phenobarbital (20mg/kg/bolus then 5mg/kg/day for 2 days) at 6 hours. Abnormal brain activity was classified as stereotypic evolving (SE) seizures, epileptiform discharges (EDs), and epileptiform transients (ETs) using continuous amplitude‐integrated electroencephalographic recordings. At 48 hours, lambs were euthanized for brain pathology. Results: Asphyxia caused abnormal brain activity, including SE seizures that peaked at 18 to 20 hours, EDs, and ETs, and induced neuronal degeneration and neuroinflammation. Ganaxolone treatment was associated with an 86.4% reduction in the number of seizures compared to the asphyxia group. The total seizure duration in the asphyxia+ganaxolone group was less than the untreated asphyxia group. There was no difference in the number of SE seizures between the asphyxia and asphyxia+phenobarbital groups or duration of SE seizures. Ganaxolone treatment, but not phenobarbital, reduced neuronal degeneration within hippocampal CA1 and CA3 regions, and cortical neurons, and ganaxolone reduced neuroinflammation within the thalamus. Interpretation: Ganaxolone provided better seizure control than phenobarbital in this perinatal asphyxia model and was neuroprotective for the newborn brain, affording a new therapeutic opportunity for treatment of neonatal seizures. ANN NEUROL 2022;92:1066–1079